Evaluation of level of preparedness and competitive activity of qualified athletes at hockey on the herbs based on signal scales - В.М. Костюкевич; И.И. Стасюк (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
The problem of building models of preparedness and competitive activity of high-qualified athletes is very important for the purposeful management of the training process. The purpose of the research is the experimental substantiation of the development of models of preparedness and competitive activity of high-qualified athletes. Material: athletes of high qualification in field hockey. Results: Based on the results of experimental studies and methods of mathematical statistics, an algorithm was developed for constructing models of preparedness and competitive activity of high-qualified athletes. Conclusions. A purposeful correction of managerial influences in the system of training highly qualified athletes should be carried out on the basis of individual, group and generalized models. The methodological approach to their development is experimentally substantiated in this study.